Effect of Plasma-Activated Water and Direct Plasma on Enterococcus faecalis Bacteria for Disinfection of Tooth Root Canal - Hameed, Tamara A.; Humud, Hammad R.; Ali, Layla F. (Iraqi Journal of Science, 2023)
This research studies the effect regarding two plasma types, plasma jet and plasma-activated water (PAW), on tooth root canal bacteria Enterococcus faecalis. The plasma jet works with argon gas, and it is generated by a power supply that operates at alternating high voltages in the form of a sinusoidal wave with peak-to-peak value of about 12 kV at a frequency of 30 KHz and its power is about 200 watts. This plasma was utilized directly to treat the tooth canal and indirectly by activating the water that was used later for treating the Enterococcus faecalis bacteria that are present in the tooth root. Pure distilled water was treated by plasma jet for one hour at flow rate 1 . Plasma water activated by plasma contains NO2, NO3, and H2O2 with a concentration (10,100,200) ppm, respectively. It was noted, as a result of direct exposure with the two values of gas flow rate and for different exposure times, an ideal killing rate (from 298 x 108 to zero)CFU/ml was obtained when the exposure time changed from (5-30) minutes with a constant gas flow rate of 2.5 ; while in the case of changing the gas flow rate from (0.5-2.5) and fixing time to 5 min, the killing rate decreased from (298 ×108 to 30×108) CFU/ml. In the case of (PAW) when the time changed (5-25) min, an ideal killing rate was obtained (298 x 108 to zero) CFU/ml; adopted one factor, where the results indicated that plasma-activated water is good in disinfecting the root canal of the tooth and inactivating bacteria.